Quality of care and patient safety at healthcare institutions: quantitative study of the perspectives of patients and healthcare assistants - Mashari Abdullah A Alshammari, Fuhaid Ytaiym R Aldhafeeri, Abdulaziz Abdullah A Alshammari, Fahhad Yataim R Aldhafeeri, Talal Issa J Albanaqi, Abdullah Shelaitan M Aldhafeeri (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The healthcare landscape has evolved significantly yet concerns about declining levels of patient safety and quality culture persist, as highlighted in a recent Quality and Patient Safety Report. This underscores the importance of evaluating care quality and patient safety through the lenses of patients and healthcare assistants.Objectives: This study aimed to explore (1) patients’ and healthcare assistants’ perceptions regarding overall care quality and patient safety standards in two tertiary hospitals and (2) the demographic factors associated with these perceptions.Methods: Using a cross-sectional design, data were gathered via the Revised Humane Caring Scale and Healthcare Professional Core Competency Instrument, assessing overall care quality and patient safety. Surveys were administered to patients (n = 600) and healthcare assistants (nurses and physicians, n = 246) across medical, surgical, and obstetrics/gynaecology departments in two tertiary hospitals between late 2018 and early 2019. Descriptive statistics and binary logistic regression were employed for data analysis.Results: A total of 367 patients and 140 healthcare assistants responded, yielding response rates of 61.2% and 56.9%, respectively. Overall, both groups perceived high levels of care quality (patients: M = 4.23, SD = 0.706; assistants: M = 4.36, SD = 0.720) and patient safety (patients: M = 4.22, SD = 0.709; assistants: M = 4.39, SD = 0.675), with assistants rating slightly higher than patients. Hospital variables were associated with care quality (OR = 0.095, 95% CI = 0.016–0.551, p = 0.009) and patient safety (OR = 0.153, 95% CI = 0.027–0.854, p = 0.032) among assistants. Admission/work area was also linked to participants’ care quality perceptions (patients, OR = 0.257, 95% CI = 0.072–0.916, p = 0.036; assistants, OR = 0.093, 95% CI = 0.009–0.959, p = 0.046).Conclusions: Both patients and healthcare assistants viewed care quality and patient safety favorably, albeit with slight variations, suggesting high levels of satisfaction and competent healthcare delivery. These insights can guide enhancements in healthcare standards, benefiting patients and healthcare systems alike